Prevalence of thyroid dysfunction in pregnant women and the need for universal screening: an observational study in Northern Andhra Pradesh population - B., Krishnamma; V., Prabhavathi; D. K. V., Prasad (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The maternal thyroid dysfunction is associated with adverse outcomes such as miscarriage, preterm delivery, preeclampsia, postpartum haemorrhage in mother whereas increased risk of impaired neurological development in foetus. The present study was designed with an aim to determine the prevalence of thyroid dysfunction and the need for universal screening in pregnant women. Methods: Three hundred and eighty pregnant women between 8-36 weeks of gestation with age group 20-32 years were recruited. Serum free T3, free T4 and TSH levels were assayed by chemiluminescence method. The pregnant women were classified into euthyroid, subclinical hypothyroid (SH), overt hypothyroid (OH) and overt hyperthyroid groups based on the results obtained in the study. Results: In the present study, the mean ± SD age (in years) and BMI of all pregnant women was 23.9±3.9 and 22.9±1.6 respectively. The maternal age was high in OH and overt hyperthyroid and was statistically significant (p<0.05). Similarly, women with high BMI were prone to OH than normal BMI (p<0.05). The prevalence of thyroid dysfunction was found to be 18.7%. The prevalence of hypothyroidism was 17.4% in which the SH was 13.4% and overt hypothyroidism 3.9%, but overt hyperthyroidism was 1.3%. TSH levels increased with the advancement of gestational age from 2.72±1.85 in first trimester to 3.4±2.05 µIU/mL in third trimester, and the difference was statistically significant (p<0.05). Finally, it was also noticed that the prevalence of raised TSH in high-risk pregnant women was high compared to low-risk women (35.6% vs 5.1%) relative risk (RR) 7.64, 95% confidence interval (CI) 4.62-12.65, (p<0.0001). However, 14 out of 51 (27.5%) with SH were in low-risk group. Conclusions: The present study states that the prevalence of thyroid dysfunction was 18.7% and also emphasizes the importance of screening all pregnant women for thyroid dysfunction rather than targeted high-risk pregnant women to prevent both maternal and fetal morbidity.